Studi Analisis Dokumen Manajemen Kurikulum dalam Pelaksanaan Projek Penguatan Profil Pelajar Pancasila (P5): Studi Kasus di SMPN 1 Tangerang - Arum Puri Suryandari; Rugaiyah; Masduki (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the form and implementation of curriculum management documents in the implementation of the Pancasila Student Profile Strengthening Project (P5) at SMPN 1 Tangerang. Using a qualitative case study approach, data were collected through documentation studies, participatory observations, and in-depth interviews with the principal, curriculum coordinator, and P5 implementing teachers. The main focus of this study is to examine the suitability of documents such as KOSP, project modules, academic calendars, and P5 Team Decrees with the principles of the Independent Curriculum. The results of the study indicate that the curriculum documents have been systematically compiled and reflect the integration of the Pancasila Student Profile values, but challenges are still found in the aspects of evaluation and cross-teacher collaboration. This study recommends the need to strengthen teacher training, optimize the role of the facilitator team, and increase document-based reflection in the management of the P5 curriculum on an ongoing basis.